Analisis Kelayakan Teknis dan Ekonomi Pembangunan Proyek Perumahan Nindya Asri 9 - Saifullah Candra Sulistiyo; Diva Hestrada Rizki Pradiga; Henny Pratiwi Adi (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Housing is a group of houses that serve as residences and are equipped with adequate facilities and infrastructure. Nindya Asri 9 Housing is a housing complex built in Sasak, Meteseh, Kendal Regency, Central Java, by PT. Nindya Karya Utama. This housing complex is planned to have 270 units with types 29-60. This study aims to analyze the technical and economic feasibility of Nindya Asri 9 Housing Complex, reviewed from a comparison of benefit costs, net present value, and other methods. The research method used in this study is descriptive and quantitative. The research data consists of primary and secondary data. The technical feasibility data processing includes the Basic Building Efficiency (KDB), Building Floor Coefficient (KLB), Basic Green Coefficient (KDB), and Green Open Space (RTH). The economic feasibility data processing includes Net Present Value (NPV), Benefit Cost Ratio (BCR), Internal Rate of Return (IRR), Payback Period (PP), and Profitability Index (PI). The analysis results of the interest rate of 10% with an investment period of 10 years. The technical feasibility of KDB is 50.2%, KLB is 0.6, KDH is 79%, and RTH is 58.4%. For economic feasibility, NPV is Rp. 5,506,655,627, BCR is 1.12113647, IRR is 17,09%, PP is 3.75 years, and PI is 1.376. This housing is feasible to use.